DISAIN BANTARAN YANG ESTETIS, EKOLOGIS DAN FUNGSIONAL DI SITU PENGARENGAN DEPOK - Qurrotu Aini Besila; Nur Intan Simangunsong; Titiek P Debora; Maria Margaretha Sintorini (Jurusan Teknik Lingkungan Fakultas Arsitektur Lanskap dan Teknologi Lingkungan, Universitas Trisakti, 2023)
Situ Pengarengan Depok has banks with the potential for the beauty of the landscape that has not been optimally utilized as a city green open space, if it is managed properly and correctly, it can be one of the alternative tourism in Depok. The problems felt by the surrounding community are (1) The occurrence of flooding in the rainy season due to silting, garbage, and plants that spread throughout the banks; (2) The lack of green open space that can be used by the community as a passive or active recreation area, (3) The lake bank has not been used optimally, and (4) There is no clarity on the authority to manage the lake bank.This Community Service (PkM) aims to (1) socialize the importance of public awareness to participate in conserving the lake and its banks, (2) making a